Pengaruh laba kotor, laba operasi, laba bersih, dan modal kerja dalam memprediksi arus kas di masa mendatang pada perusahaan infrastruktur yang terdaftar di Bursa Efek Indonesia Periode 2016-2019 - Aritonang, Putri Yunita; Arisandy Aruan, Deasy; Sari Manurung, Renta; Siti Azzahra , Tifa; Rosanti Pasaribu, Lisa (Jurnal Paradigma Ekonomika, 2022)
This study aims to understand the effect of gross profit, operating profit, net profit, and working capital on future cash flows in infrastructure companies listed on the Indonesia Stock Exchange for the 2016-2019 period. This research uses quantitative methods. The data used is secondary data obtained through the websiteÂ www.IDX.co.id. The analytical method used is the multiple linear regression analysis method. The results obtained partially gross profit and net profit have a positive and significant effect on cash flows in the future. Meanwhile, operating profit and working capital have no significant effect on future cash flows. Simultaneously gross profit, operating profit, net profit, and working capital have a significant effect on future cash flows in infrastructure companies listed on the Indonesia Stock Exchange for the 2016-2019 period.